This Old House: Penal Substitution and the Justice Worry - Thurow, Joshua C. (Philosophia Christi, 2025)
William Lane Craig has put a lot of clever work into trying to remodel and restore the penal substitution view of atonement. I argue, however, that Craig has fallen into a money pit. His penal substitutionary view is vulnerable to two versions of the justice worry. And his case for his view is methodologically flawed; it assumes biblical Mooreanism, which I argue does not apply in theorizing about atonement. I present a better, inference to the best explanation, theological methodology and suggest that on it other atonement theories fare better than penal substitution.